(untitled) (Scientific journal of the Fergana State University, 2026)
Seed germination under saline and arid conditions is often limited due to stress factors, which highlights the need for effective approaches to enhance plant resilience. This study aimed to evaluate the effects of silicon-based and biologically active preparations Aminosid-Silicon, Aminosid-Aton, and Bionitrogen applied to cotton (Gossypium hirsutum L., cv. Bukhara-8). Germination dynamics were monitored from 10 to 22 days after sowing, and significant improvements were recorded in the treatment groups. Among them, Aminosid-Silicon showed the highest germination rate (79.3%), compared to 65.3% in the untreated control. Biochemical analysis revealed that silicon treatments stimulated the activity of antioxidant enzymes such as superoxide dismutase (SOD), catalase (CAT), and peroxidase (POD), as well as enhanced proline accumulation in seedlings. These results confirm that silicon-based preparations can compensate for native silicon deficiency in soils and play a key role in improving seed germination and enhancing physiological defense mechanisms under saline and arid stress conditions. Specifically, Aminosid-Silicon treatment increased superoxide dismutase activity from 143.12 to 158.69 U/mg protein, catalase from 81.78 to 103.21 U/mg protein, peroxidase from 134.96 to 152.01 U/mg protein, and proline content from 112.3 to 144.7 μg/g fresh weight, indicating a significant enhancement in physiological defense mechanisms under stress conditions.